Patient Satisfaction Analysis Using Methods Importance Performance Analysis and Customer Satisfaction Index in Hospital Dr. Pirngadi Medan - Nawirah, Luthfiah; Delvika, Yuana; Sutrisno, Sutrisno (Universitas Medan Area, 2024)
This research was conducted to determine the level of consumer satisfaction with the services of Regional General Hospital and to find out what attributes were the main priorities in improving service quality to improve service quality in Dr. Pirngadi Regional General Hospital, by distributing closed questionnaires and calculating using the Importance Performance Analysis (IPA) method and the Customer Satisfaction Index (CSI) methods. From the calculation results of the Importance Performance Analysis (IPA) method, it had a conformity level value of 60.653% and in the Cartesian Chart of the 20 attributes, 8 attributes required repairing and improvement, namely attributes number 2, 6, 8, 9, 10, 11, 18 and 20. The calculation results of the Customer Satisfaction Index (CSI) method of Dr.Pirngadi Regional General Hospital Medan gained a score of 39.03% indicating that the customers of Dr.Pirngadi Regional General Hospital Medan who had felt